A Matter of Scale: Responses to Landscape Changes in the Oslo Fjord, Norway, in the Mesolithic - Mjærum Axel (Open Archaeology, 2022)
Present-day global warming has great consequences, both for individuals and on a larger scale for society as a whole. However, environmental changes also affected everyday life in the past. The purpose of this article is to apply perspectives developed in studies of how contemporary societies adapt to shore-level changes and to use this insight in a study of the way Mesolithic populations handled a situation of large land uplift. More specifically, the author discusses four common adaptation strategies devised to cope with changing sea level, both on a site level and on a regional scale – to accommodate, relocate, protect, or not respond to the changing environment. In the Oslo Fjord in Norway, the shorelines moved from approximately 200–40 m above the present-day sea level in the period 9300–3900 cal BC, caused by the strong post-glacial rebound. Along the shores lived populations that based much of their life on the local marine resources. Building on information from the large habitation area Havsjødalen and a statistical analysis of 529 critically selected sites in the region, the author concludes that single sites were systematically accommodated or relocated when the distance to the shores receded. However, sea level changes caused more dramatic regional landscape transformation and a less bountiful environment c. 5000 cal BC, with a period of maladaptation and a subsequent population collapse as a result. Like modern societies facing human-caused climate changes, the Mesolithic population had difficulties in handling the need for large-scale shifts in their society.